Feedback-related negativity observed in rodent anterior cingulate cortex. Issue 1 (February 2015) - Warren, Christopher M.; Hyman, James M.; Seamans, Jeremy K.; Holroyd, Clay B.
Highlights: We record local field potentials from the rodent anterior cingulate. We find rodent ACC is sensitive to feedback indicating impending reward. We find rodent ACC is sensitive to outcome probability. We identify the rodent homologue of the feedback-related negativity observed in humans. Abstract: The feedback-related negativity (FRN) refers to a difference in the human event-related potential (ERP) elicited by feedback indicating success versus failure: the difference appears negative when subtracting the success ERP from the failure ERP (Miltner et al., 1997). Although source localization techniques (e.g., BESA) suggest that the FRN is produced in the ACC, the inverse problem (that any given scalp distribution can be produced by an infinite number of possible dipole configurations) limits the certainty of this conclusion. The inverse problem can be circumvented by directly recording from the ACC in animal models. Although a non-human primate homologue of the FRN has been observed in the macaque monkey (e.g. Emeric et al., 2008), a homologue of the FRN has yet to be identified in rodents. We recorded local field potentials (LFPs) directly from the ACC in 6 rodents in a task based on the FRN paradigm. The animals were trained to poke their nose into a lighted port and received a feedback smell indicating whether or not a reward pellet would drop 1.5 s later. We observed a FRN-like effect time-locked to the feedback scent whereby the LFP to feedback predicting no-reward was significantly more negative than the LFP to feedback predicting reward. This deflection began on average 130 ms before behavioral changes in response to the feedback. Thus, we provide the first evidence of the existence of a rodent homologue of the FRN.